Toward the Meeting of the Waters : Currents in the Civil Rights Movement of South Carolina during the Twentieth Century - Burton, Orville Vernon; Moore, Winfred B., 1949- (Book collections on Project MUSE., 2008)
Brings together voices of leading historians alongside recollections from central participants to provide the first comprehensive history of the civil rights movement as experienced by black and white South Carolinians. --from publisher descriptioin.